Development of a nonhuman primate challenge model to evaluate CD8+ T cell responses to an adenovirus-based vaccine expressing SIV proteins upon repeat-dose treatment with checkpoint inhibitors - Richard Graveline; Morad Haida; Carolyne Dumont; Dominic Poulin; Florence Poitout-Belissent; Rana Samadfam; Sven Kronenberg; Franziska Regenass-Lechner; Rodney Prell; Marie-Soleil Piche (Taylor & Francis Group, 2022)
Targeting immune checkpoint receptors expressed in the T cell synapse induces active and long-lasting antitumor immunity in preclinical tumor models and oncology patients. However, traditional nonhuman primate (NHP) studies in healthy animals have thus far demonstrated little to no pharmacological activity or toxicity for checkpoint inhibitors (CPIs), likely due to a quiescent immune system. We developed a NHP vaccine challenge model in Mauritius cynomolgus monkey (MCMs) that elicits a strong CD8+ T cell response to assess both pharmacology and safety within the same animal. MHC I-genotyped MCMs were immunized with three replication incompetent adenovirus serotype 5 (Adv5) encoding Gag, Nef and Pol simian immunodeficiency virus (SIV) proteins administered 4 weeks apart. Immunized animals received the anti-PD-L1 atezolizumab or an immune checkpoint-targeting bispecific antibody (mAbX) in early development. After a single immunization, Adv5-SIVs induced T-cell activation as assessed by the expression of several co-stimulatory and co-inhibitory molecules, proliferation, and antigen-specific T-cell response as measured by a Nef-dependent interferon-γ ELIspot and tetramer analysis. Administration of atezolizumab increased the number of Ki67+ CD8+ T cells, CD8+ T cells co-expressing TIM3 and LAG3 and the number of CD4+ T cells co-expressing 4-1BB, BTLA, and TIM3 two weeks after vaccination. Both atezolizumab and mAbX extended the cytolytic activity of the SIV antigen-specific CD8+ T cell up to 8 weeks. Taken together, this vaccine challenge model allowed the combined study of pharmacology and safety parameters for a new immunomodulatory protein-based therapeutic targeting CD8+ T cells in an NHP model.